2017
DOI: 10.1038/s41467-017-00726-x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor induces muscle wasting in mice through releasing extracellular Hsp70 and Hsp90

Abstract: Cachexia, characterized by muscle wasting, is a major contributor to cancer-related mortality. However, the key cachexins that mediate cancer-induced muscle wasting remain elusive. Here, we show that tumor-released extracellular Hsp70 and Hsp90 are responsible for tumor’s capacity to induce muscle wasting. We detected high-level constitutive release of Hsp70 and Hsp90 associated with extracellular vesicles (EVs) from diverse cachexia-inducing tumor cells, resulting in elevated serum levels in mice. Neutralizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
243
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(255 citation statements)
references
References 57 publications
11
243
0
1
Order By: Relevance
“…Cancer cachexia is initiated by tumour‐derived factors . There is general consensus that many of these factors are proteins . We previously showed that LIF is not only sufficient to induce myotube atrophy, but it is entirely responsible for atrophy due to treatment with C26 tumour cell CM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cachexia is initiated by tumour‐derived factors . There is general consensus that many of these factors are proteins . We previously showed that LIF is not only sufficient to induce myotube atrophy, but it is entirely responsible for atrophy due to treatment with C26 tumour cell CM .…”
Section: Discussionmentioning
confidence: 99%
“…Not all preclinical models of cachexia involve LIF. The Lewis Lung Carcinoma (LLC) is another well‐studied mouse model of cancer cachexia, and several tumour‐secreted proteins, other than LIF, have been implicated in causing wasting from LLC . Our own evaluation of CM from LLC shows that they secrete very low levels of LIF, not enough to contribute to wasting (see ).…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock protein 70 (Hsp70) is a predominantly intracellular protein, but can be released externally, especially under disease or stress conditions to stimulate a proinflammatory response . Increased levels of Hsp70 were found in secreted exosomes in different disease states, including cancer, bacterial infection, and sarcoidosis, and these exosomes could induce pro‐inflammatory or immunostimulatory responses, such as NF‐κB activation and TNF‐α release or increased IFN‐γ and IL‐13 production …”
Section: Role Of Exosomesmentioning
confidence: 99%
“…Zhang et al . (2017) suggested that tumour‐derived exosomes may be responsible for the induction of cachexia . A plethora of studies show that inflammatory mediators, including tumour necrosis factor‐α (TNF‐α), interferon‐γ (IFN‐γ), interleukin (IL)‐1 and IL‐6, myostatin, and transforming growth factor β (TGF‐β) are involved in the etiology of the loss of skeletal muscle and adipose tissue mass.…”
Section: Introductionmentioning
confidence: 99%